(R,R)-N-phenyl-3,4-bis(diphenylphosphino)pyrrolidine: an N-aryl pyrrolidine ligand for enantioselective transfer hydrogenation - Gonsalves, António Manuel d'Albuquerque Rocha (2001)
The N-aryl pyrrolidine diphosphine (R,R)-N-phenyl-3,4-bis(diphenylphosphino)pyrrolidine was obtained from natural tartaric acid. Contrary to our preliminary expectations, this new chiral ligand proved to be less selective than the corresponding N-benzyl pyrrolidine diphosphine. An attempted explanation of the observed behaviour based on the stereochemistry of the ligand as shown by X-ray crystallography is presented.